“Science and Art. The Painted Surface” by Antonio Sgamellotti, Brunetto Giovanni Brunetti y Costanza Miliani (Eds.) - Gonzales Gil, Patricia (2016)
Short review of the most important and interesting sections of the multidisciplinary science book that we strongly recommend: "Science and Art. The Painted Surface”.